2006
DOI: 10.1111/j.1440-1754.2006.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric tuberculosis in a Pacific Islands community in New Zealand

Abstract: Children are at high risk of developing active disease after exposure to TB. The study describes the minimal symptoms manifested in many of the children with significant radiological changes consistent with pulmonary TB. This highlights the need to consider Mantoux testing and chest X-rays for children presenting with persistent respiratory symptoms in high-risk populations. Issues of contact tracing and adherence were also a problem in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…7 The high proportion of infected children in the Young Group, 83%, is comparable to what was previously seen within households and in a day care center outbreak. 8,9 It implies that the contact between care providers and children at a day care center is at the same risk level for transmission as within a household setting. If a center is used by more children, parents, and staff than it was originally designed for, this risk is often higher.…”
Section: Discussionmentioning
confidence: 99%
“…7 The high proportion of infected children in the Young Group, 83%, is comparable to what was previously seen within households and in a day care center outbreak. 8,9 It implies that the contact between care providers and children at a day care center is at the same risk level for transmission as within a household setting. If a center is used by more children, parents, and staff than it was originally designed for, this risk is often higher.…”
Section: Discussionmentioning
confidence: 99%
“…The auckland regional public health service worked extremely hard to limit the spread of tb and to treat all involved but they were hampered by inter-household movement, difficulties in tracing people, and unfamiliarity with this 'new' pacific community. in a few cases, people were reluctant to declare themselves to authorities, perhaps because of their immigration status or the stigma surrounding tb (or all of the above) (Voss et al, 2006). ng shiu (2008) and hay (2009) who, in conjunction with our project, carried out research in auckland with pacific people, including tuvaluans, found that all these factors were important contributors to diagnostic delay and difficulties in contact tracing.…”
Section: The Outbreakmentioning
confidence: 86%
“…large interconnected families were caught up in it. They were linked in several ways and particularly though a woman (the initial source), the mother of the child first diagnosed, who herself had undiagnosed active pulmonary tb disease for several months and had stayed in several different households, providing informal help with childcare (Voss et al, 2006). The auckland regional public health service worked extremely hard to limit the spread of tb and to treat all involved but they were hampered by inter-household movement, difficulties in tracing people, and unfamiliarity with this 'new' pacific community.…”
Section: The Outbreakmentioning
confidence: 99%
See 2 more Smart Citations